Orphans on the earth : Girondin fugitives from the Terror, 1793-1794 - Oliver, Bette Wyn, 1933- (Lexington Books, 2009)
Just as it was not foreordained that the Terror of 1793-1794 should follow the early idealistic years of the French Revolution, neither could it have been imagined that some of those elected deputies who had helped to establish the new republic would become fugitives from their own government. Yet, in May to June 1793, twenty-nine deputies of the moderate Girondin faction were expelled from the National Convention by the radical Jacobin leadership and placed under house arrest. This action followed monthsof irreconcilable quarrels between the Girondin and Jacobin factions. Some of the proscrib.